Randomized Comparison of Pramlintide or Mealtime Insulin Added to Basal Insulin Treatment for Patients With Type 2 Diabetes - Riddle, Matthew (American Diabetes Association, 2009)
OBJECTIVE: To compare the efficacy and safety of adding mealtime pramlintide or rapid-acting insulin analogs (RAIAs) to basal insulin for patients with inadequately controlled type 2 diabetes. RESEARCH DESIGN AND METHODS: In a 24-week open-label, multicenter study, 113 patients were randomly assigned 1:1 to addition of mealtime pramlintide (120 μg) or a titrated RAIA to basal insulin and prior oral antihyperglycemic drugs (OADs). At screening, patients were insulin naive or had been receiving <50 units/day basal insulin for <6 months. The basal insulin dosage was titrated from day 1, seeking fasting plasma glucose (FPG) ≥70–<100 mg/dl. Pramlintide and an RAIA were initiated on day 1 and week 4, respectively. The proportion of patients achieving A1C ≤7.0% without weight gain or severe hypoglycemia at week 24 was the primary end point. RESULTS: More pramlintide- than RAIA-treated patients achieved the primary end point (30 vs. 11%, P = 0.018) with a similar dose of basal insulin. Pramlintide and an RAIA yielded similar mean ± SEM values for FPG and A1C at 24 weeks (122 ± 7 vs. 123 ± 5 mg/dl and 7.2 ± 0.2 vs. 7.0 ± 0.1%, respectively) and similar least squares mean reductions from baseline to end point (−31 ± 6 vs. −34 ± 6 mg/dl and −1.1 ± 0.2 vs. −1.3 ± 0.2%, respectively). RAIAs but not pramlintide caused weight gain (+4.7 ± 0.7 vs. +0.0 ± 0.7 kg, P < 0.0001). Fewer patients reported mild to moderate hypoglycemia with pramlintide than with the RAIA (55 vs. 82%), but more patients reported nausea (21 vs. 0%). No severe hypoglycemia occurred in either group. CONCLUSIONS: In patients taking basal insulin and OADs, premeal fixed-dose pramlintide improved glycemic control as effectively as titrated RAIAs. The pramlintide regimen sometimes caused nausea but no weight gain and less hypoglycemia.